Assessing the market channel performance of Colorado fruit and vegetable producers - Christensen, Jeremiah Q., author; Thilmany, Dawn, advisor; Jablonski, Becca, advisor; Uchanski, Mark, committee member (Colorado State University. Libraries, 2017)
The growing popularity of locally sourced fruits and vegetables in the United States provides an opportunity for small and mid-sized farms to improve viability through sales to local markets. However, there is little research that looks at differences in business performance in these markets, and specifically, how labor allocation and marketing expenditures may vary by market. Based on the Market Channel Assessment Tool (MCAT) protocol developed in New York, variable costs (except those associated with production) and revenues were collected via market channel through farm interviews and labor logs recorded by producers during a one-week period spanning the peak marketing season in 2016 in Colorado. Following the New York model, it is expected that richer cost and revenue information can be used to support improved market decisions related to balancing market channel portfolios for individual farm participants. Moreover, aggregated data was used to establish performance benchmarks by market channel and region for producers to use for comparisons to peers. In addition, a two-dimensional fixed effect model quantified the impact of farm level attributes on market channel profitability. Results indicate channel profitability is positively impacted by the share of harvest labor involved in marketing and number of market channels, while negatively impacted by the share of labor facilitating sales (staffing market stands or making calls to buyers) and the number of crops grown. Extension agents and other agriculture support providers can use these results to support more involved farm market channel decision-making and efficient variable input expenditure recommendations.
Keywords: benchmarking; local food systems; specialty crops; farming; agricultural marketing; market channel assessment